Efficacy and safety of whole-body vibration therapy for post-stroke spasticity: A systematic review and meta-analysis - Zhang, Qi; Zheng, Shuqi; Li, Shuiyan; Zeng, Yuting; Chen, Ling; Li, Gege; Li, Shilin; He, Longlong; Chen, Shuping; Zheng, Xiaoyan; Zou, Jihua; Zeng, Qing (Frontiers in Neurology, 2023)
Background One of the main objectives of stroke rehabilitation is to alleviate post-stroke spasticity. Over the recent years, many studies have explored the potential benefits of whole-body vibration (WBV) treatment for post-stroke spasticity, but it is still controversial. Objective The current study aims to assess the efficacy and safety of WBV for post-stroke spasticity and determine the appropriate application situation. Methods From their establishment until August 2022, the following databases were searched: PubMed, Web of Science, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Medline, China National Knowledge Infrastructure (CNKI), and Wanfang. Only randomized controlled trials (RCTs) that were published in either English or Chinese were taken into consideration. We independently filtered the research, gathered the data from the studies, and evaluated the research quality (Cochrane RoB tool) and the overall evidence quality (GRADE). Rev Man 5.4 software was utilized to conduct statistical analysis. Results In this analysis, 11 RCTs with 475 patients that reported on the effectiveness of WBV therapy for post-stroke spasticity were taken into account. Compared to the control groups, the results revealed that WBV combined with conventional rehabilitation at a vibration frequency lower than 20 Hz (SMD = −0.58, 95% CI: −0.98 to −0.19, P = 0.004) was more effective in relieving upper (SMD = −0.53, 95% CI: −1.04 to 0.03, P = 0.03) and lower limb spasticity (SMD = −0.21, 95% CI: −0.40 to −0.01, P = 0.04); similarly, it was superior for patients aged under 60 years (SMD = −0.41, 95% CI: −0.66 to −0.17, P = 0.0008) with acute and subacute stroke (SMD = −0.39, 95% CI: −0.68 to −0.09, P = 0.01). The valid vibration for reducing spasticity was found to last for 10 min (SMD = −0.41, 95% CI: −0.75 to −0.07, P = 0.02). None of the included studies revealed any serious adverse impact. Conclusion Moderate-quality evidence demonstrated when WBV was used as an adjuvant, vibration <20 Hz for 10 min was effective and secure in treating upper and lower limb spasticity in patients with acute and subacute stroke under the age of 60 years. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022293951.